1994
DOI: 10.1002/ange.19941060905
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilie‐ und Elektrophilieskalen als Ordnungsprinzipien polarer organischer und metallorganischer Reaktionen

Abstract: Das hundertjährige Bestehen feiert im Mai in Berlin die BÜCHER -=Chemistry Imagined: Reflections on Science · R. Hoffmann, V. TorrenceDictionary of Trivial Names/Trivialnamen-Handbuch. Band 1-3 * Fa ch i η fο r m a t i ο η sze η t rum Chemie Chemical Vapor Deposition. Principles and Applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
23

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 293 publications
(192 citation statements)
references
References 143 publications
5
164
0
23
Order By: Relevance
“…with anisole, for instance, is predicted from the tables of Mayr and Patz, [7] a reaction which was indeed observed experimentally. [13] For the rather electrophilic chloromethylene iminium salt (Vilsmeier-Haack ion) Mayr and Ofial [8] report an E parameter of -4.8, which indicates that this cation is about four times less reactive than the cumulene ion 1b ؉ .…”
Section: ⋅Kmentioning
confidence: 69%
See 2 more Smart Citations
“…with anisole, for instance, is predicted from the tables of Mayr and Patz, [7] a reaction which was indeed observed experimentally. [13] For the rather electrophilic chloromethylene iminium salt (Vilsmeier-Haack ion) Mayr and Ofial [8] report an E parameter of -4.8, which indicates that this cation is about four times less reactive than the cumulene ion 1b ؉ .…”
Section: ⋅Kmentioning
confidence: 69%
“…For the comparison of electrophilic reactivities of different cations towards known nucleophiles the LFER lg k 20°C ϭ s (E ϩ N) developed by Mayr and Patz [7] has proven to be of great interpretive and predictive value. After extrapolation of the rate constant for the reaction of 1b ؉ ⋅CF 3 SO 3 -with 1,4-cyclohexadiene to 20°C from temperature dependent rate measurements (Arrhenius plot; activation parameters:…”
Section: Electrophilicity Parameters Ementioning
confidence: 99%
See 1 more Smart Citation
“…Die Rückreaktion mit der Geschwindigkeit v_, ist als termolekularer Prozeß kinetisch benachteiligt, so daß sie ausgeschlossen werden kann. 41 Weitere Experimente zur Transferhydrogenolyse ergaben, daß abgesehen von Triphenyl-, Diphenylfluormethan und Benzylfluorid auch 1-Adamantyl(diphenylmethyl)chlorid mit 9,10-Dihydroanthracen 2 unter H-Atom-Übertragung reagiert. Die Triebkraft der Transferhydrogenolyse mit Fluoriden beruht zweifellos auf der hohen Bindungsenthalpie von HF (136 kcal mol -1 der Literatur durch Studien zum Mechanismus überprüft und gestützt oder ergänzt werden.…”
Section: Transferhydrogenolyseunclassified
“…It has already been demonstrated that bicyclo [2,2,1]heptene (norbornene) is one of the most versatile model olefins in studies of the role of reagent structure of electron acceptor type E-L reagents on the course of the addition reaction. [1][2][3][4][5][6] From these studies, two types of information can be obtained: the structures of the products and their distribution inform us about the type of electron shift from the π electron system to acceptor E-L reagent;1-6 the relative rates of functionalisation of norbornene versus cyclohexene inform us about the geometry of the rate determining transition state, 7 being insensitive in the case of a three-centered intermediate (mercuric acetate 8 ), but very sensitive for four-centered or larger intermediates in (picryl azide 9 a rate ratio up to 8 .…”
Section: Introductionmentioning
confidence: 99%